The 23rd Annual Vancouver Folk Music Festival - Vancouver Folk Music Festival Societyet al (2000)
Jericho Beach Park The 23rd Annual Vancouver folk music FESTIVAL/ Design: The Insight Group/ music from across the street and around the world deep roots Music and dance of the First Nations, the Metis, Quebec, Cape Breton and Newfoundland the Young celtic edge The hottest young bands from Quebec, Cape Breton, Ireland and Norway dance 'til you drop to the music of Brazil, Africa, Rajasthan, red hot Klezmer and step-dancing fiddlers. raising the spirit with gospel song and First Nations dance. seven stages with over 70 hours of music featuring the return of La Bottine Souriante, the Dancers of the Kwakwaka'wakw, Uganda's Christ The King Church Choir, Linda Tillery and the Cultural Heritage Choir, songs of the working folk from Solidarity Notes, the big band sounds of Alpha Ya Ya Diallo, the blues of Carlos del Junco, the songs of Eastern Europe with Zeellia and music from the past and the future from the Medieval Baebes, guitar gods Kevin Breit, Freddie Roulette, Andre Thibault and Ralph Towner . and much much more!/ July 14-16 2000 Jericho Beach Park, Vancouver, B.C./ tickets@ With no service charge from Festival office in Vancouver, 100 - 207 West Hastings p 604-602-9798 f 604-602-9790 toll free Can/US: 1-800-883-FOLK (3655) www.thefestival.bc.ca/ OTHER OUTLETS Service charges may apply TicketMaster across Canada. Vancouver: 280-4444. Victoria: 386-7600. Kelowna: 860-1470. Prince George: 614-9100. Kamloops: 374-9200. Seattle: 628-0888. Portland: 224-4400. www.ticketmaster.ca; www.ticketmaster.com VANCOUVER Black Swan Records, 3209 West Broadway, 734-2828. Highlife Records, 1317 Commercial Drive, 251-6964. VICTORIA Boomtown Import Records & CDs, #102 - 561 Johnson Street, 380-5090. SALT SPRING ISLAND The Music Emporium, 149 Fulford-Ganges Road, in Ganges, 537-9129. TRAIL Selkirk Computers, 1598 Bay Avenue, 368-3033. SEATTLE Cellophane Square, 4538 University Way NE, 634-2280 and 130 Broadway Ave East, 329-2233. BELLEVUE Cellophane Square, 169 Bellevue Square, 454-5059. BELLINGHAM Cellophane Square, 115 East Magnolia, 676-1404. MOUNT VERNON Northern Lights, 402 South 1st Street, 336-0161. PORTLAND Crossroads Music, 3130-B SE Hawthorne Blvd., 232-1767./ BRITISH COLUMBIA ARTS COUNCIL Supported by the Province of British Columbia/ Canadian Heritage Patrimoine canadien/ Granville Island/ TOM LEE Music/ happy planet fresh juices & smoothies/ Insight The Insight Group Public Affairs/Marketing/Advertising Inc./ waterstreet TECHNOLOGIES/ THE GEORGIA straight VANCOUVER'S NEWS & ENTERTAINMENT WEEKLY/ CBC Television British Columbia/ CBC radio ONE 690 VANCOUVER/ the loop magazine/ Produced by the Vancouver Folk Music Festival Society, with the generous financial assistance of the City of Vancouver, through the Board of Parks and Recreation, and the Office of Cultural Affairs, Social Planning Department; the Province of British Columbia through the British Columbia Arts Council and gaming revenue; the Government of Canada through the Department of Canadian Heritage - Cultural Initiatives Program; CMHC Granville Island and the Granville Island Community; and our Festival Partners.